Access to health services, health conditions and exposure to risk factors: perception of riparian fishermen of the Machado River in Ji-Paraná, RO - Prosenewicz, Ivania; Lippi, Umberto Gazi (Saúde e Sociedade, 2012)
This paper presents a study about the perceptions of riparian fishermen in the city of Ji-Paraná, Northern Brazil, in relation to their access to the health services of the local public network. In addition, it aims to identify this population's perceptions concerning health conditions and their exposure to risk factors. It is a qualitative, analytical-descriptive research. For data collection, semi-structured interviews and free observation were conducted in home visits in the period of September, October and November 2009, with 23 fishermen (15 men and 8 women). The interviewed population notices they are exposed to several risks and health problems, mainly in the flood period. In their work, there are risks of accidents, drowning and others hazards, due to lack or insufficiency in relation to the use of Individual Protection Equipments - IPE. The majority of the interviewees (19) reported health problems, like back pain, pain in the legs, muscular pain, cramps, sight problems, headaches, flu and skin diseases. The riparian fishermen who participated in the research identify many difficulties in their access to the public health services and deficiencies in basic sanitation. Besides, the researched area is not covered by the Family Health Strategy. Thus, it is necessary to formulate policies that enable the improvement in infrastructure, the reduction in health care inequalities and the expansion of the Family Health Strategy.